Insights into the C Distribution in Si:C/Si:C:P and the Annealing Behavior of Si:C Layers. (18th April 2019) - Dhayalan, Sathish Kumar; Nuytten, Thomas; Pourtois, Geoffrey; Simoen, Eddy; Pezzoli, Fabio; Cinquanta, Eugenio; Bonera, Emiliano; Loo, Roger; Rosseel, Erik; Hikavyy, Andriy; Shimura, Yosuke; Vandervorst, Wilfried
Abstract : Si:C and Si:C:P alloys are potential candidates for source-drain stressor applications in n-type Fin Field Effect Transistors (FinFETs). Increasing the C content to achieve high strain results in the arrangement of C atoms as third nearest neighbors (3nn) in the Si:C lattice. During thermal annealing, the presence of C atoms as 3nn may promote clustering at the interstitial sites, causing loss of stress. The concentration of C atoms as 3nn is reduced by the incorporation of a small amount of Ge atoms during the growth, whereas in-situ P doping does not influence this 3nn distribution [J Solid State Sci. Technol vol 6, p 755, 2017]. Small amounts of Ge are provided during low temperature selective epitaxial growth scheme, which are based on cyclic deposition and etching (CDE). In this work, we aim to provide physical insights into the aforementioned phenomena, to understand the behavior of 3nn C atoms and the types of defects that are formed in the annealed Si:C films. Using ab-initio simulations, the Ge-C interaction in the Si matrix is investigated and this insight is used to explain how the Ge incorporation leads to a reduced 3nn distribution of the C atoms. The interaction between C and P in the Si:C:P films is also investigated to explain why the P incorporation has not led to a reduction in the 3nn distribution. We then report on the Raman characterization of Si:C layers subjected to post epi annealing. As the penetration depth of the laser is dependent on the wavelength, Raman measurements at two different wavelengths enable us to probe the depth distribution of 3nn C atoms after applying different annealing conditions. We observed a homogeneous loss in 3nn C throughout the layer. Whereas in the kinematic modeling of high resolution X-ray diffraction spectra, a gradient in the substitutional C loss was observed close to the epitaxial layer/substrate interface. This gradient can be due to the out diffusion of C atoms into the Si substrate or to the formation of interstitial C clusters, which cannot be distinguished in HR-XRD. Deep Level Transient Spectroscopy indicated that the prominent out-diffusing species was interstitial CO complex while the interstitial C defects were also prevalent in the epi layer.